2015
DOI: 10.1038/srep15874
|View full text |Cite
|
Sign up to set email alerts
|

Associations between occupation exposure to Formaldehyde and semen quality, a primary study

Abstract: Formaldehyde (FA), a ubiquitous environmental pollutant, has long been suspected of having male reproductive toxicity. However, FA male reproductive toxicity was inconclusive due to dearth of human studies. Therefore, we sought to investigate whether occupational exposure to FA affects semen quality. Semen quality including five conventional parameters and seven kinematics parameters were compared between 114 male workers occupationally exposed to FA and 76 referents. FA exposure index (FEI) was measured and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
(66 reference statements)
2
23
1
Order By: Relevance
“…Recent studies reported that industrial workers could still be exposed to several parts per million of FA. For instance, FA exposure levels ranged from to in a wood processing factory and from to in a utensil factory ( Wang et al 2015 ; Zhang et al 2010b ). The International Agency for Research on Cancer (IARC) classified FA as a Group 1 human carcinogen ( IARC 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that industrial workers could still be exposed to several parts per million of FA. For instance, FA exposure levels ranged from to in a wood processing factory and from to in a utensil factory ( Wang et al 2015 ; Zhang et al 2010b ). The International Agency for Research on Cancer (IARC) classified FA as a Group 1 human carcinogen ( IARC 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Logarithmic transformation was performed for total sperm count and sperm concentration with nonnormal distribution. Confounding factors for the regression were based on their importance in the literature and biological plausibility (Li et al, 2009; Liu et al, 2012; Wang et al, 2015), which including age, length of service, smoking status, BMI, alcohol intake, duration of abstinence, education, and offspring’s birth weight.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term exposure to formaldehyde and VOCs results in acute diseases, such as irritating responses of eyes, respiratory symptoms, headache, tiredness and asthma symptoms 1 2 3 . Study also revealed the adverse effects of formaldehyde exposure on semen quality 4 . Long-term exposure to these pollutants will even cause cancer 5 .…”
mentioning
confidence: 92%
“…Poor indoor air quality caused by formaldehyde and volatile organic compounds (VOCs) from building materials may give rise to decreased work efficiency and health-related problems 1 2 3 4 5 6 7 . Short-term exposure to formaldehyde and VOCs results in acute diseases, such as irritating responses of eyes, respiratory symptoms, headache, tiredness and asthma symptoms 1 2 3 .…”
mentioning
confidence: 99%